2020
DOI: 10.1073/pnas.1918445117
|View full text |Cite
|
Sign up to set email alerts
|

Hepsin enhances liver metabolism and inhibits adipocyte browning in mice

Abstract: Hepsin is a transmembrane serine protease primarily expressed in the liver. To date, the physiological function of hepsin remains poorly defined. Here we report that hepsin-deficient mice have low levels of blood glucose and lipids and liver glycogen, but increased adipose tissue browning and basal metabolic rates. The phenotype is caused by reduced hepatocyte growth factor activation and impaired Met signaling, resulting in decreased liver glucose and lipid metabolism and enhanced adipocyte browning. Hepsin-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 55 publications
4
45
1
Order By: Relevance
“…The mice also had high food and water intakes, which is in an agreement with a high basal metabolic rate [78]. Further studies in hepsin KO mice identified an adipose browning phenotype, as indicated by low adipose weights, small adipocyte sizes, increased glucose uptakes, and high levels of brown adipocyte markers (Ucp1, uncoupling protein 1 and Cidea, cell death-inducing DFFA-like effector A) in both white and brown adipose tissues [78]. Brown adipocytes are mitochondria-rich, thermogenic, and metabolically active.…”
Section: Adipose Tissuessupporting
confidence: 75%
See 3 more Smart Citations
“…The mice also had high food and water intakes, which is in an agreement with a high basal metabolic rate [78]. Further studies in hepsin KO mice identified an adipose browning phenotype, as indicated by low adipose weights, small adipocyte sizes, increased glucose uptakes, and high levels of brown adipocyte markers (Ucp1, uncoupling protein 1 and Cidea, cell death-inducing DFFA-like effector A) in both white and brown adipose tissues [78]. Brown adipocytes are mitochondria-rich, thermogenic, and metabolically active.…”
Section: Adipose Tissuessupporting
confidence: 75%
“…Latest studies indicate that the primary function of hepsin in the liver is to regulate glucose, lipid, and protein metabolism [78]. Hepsin KO mice have low levels of liver glycogen and triglyceride, blood glucose, and serum triglyceride, free fatty acids, and cholesterol.…”
Section: Livermentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the expression of MET, a specific receptor of HGF, can also be upregulated by hepsin. 14,42 Accumulating evidence has demonstrated that the miR-222 level is increased by MET. 20,21 Based on these data, we hypothesize that miR-222 can be modulated by hepsin.…”
Section: Discussionmentioning
confidence: 99%